1982
DOI: 10.4141/cjps82-146
|View full text |Cite
|
Sign up to set email alerts
|

Selective Control of Canada Thistle in Rapeseed With 3,6-Dichloropicolinic Acid

Abstract: o'Sur-r-rveNl, P. A. axo Kossarz, v. c. 1982. Selective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Effective kill of the root system of C. arvense with 3,6-dichloropicolinic acid at 0-2-0-8 kg ha~' has been reported (O'Sullivan & Kossatz, 1982). In the present study it would appear that sensitivity of the roots rather than effective transport of large amounts of 3,6-dichloropicolinic acid into the root system of C. arvense may be relatively more important for effective root kill since little radioactivity (approximately 8%) of • Numbers within columns followed by the same letter are not significantly different at the 5% level according to Duncan's multiple range test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective kill of the root system of C. arvense with 3,6-dichloropicolinic acid at 0-2-0-8 kg ha~' has been reported (O'Sullivan & Kossatz, 1982). In the present study it would appear that sensitivity of the roots rather than effective transport of large amounts of 3,6-dichloropicolinic acid into the root system of C. arvense may be relatively more important for effective root kill since little radioactivity (approximately 8%) of • Numbers within columns followed by the same letter are not significantly different at the 5% level according to Duncan's multiple range test.…”
Section: Discussionmentioning
confidence: 99%
“…One composite, Cirsium arvense L, (Scop,) is the most serious perennial weed in cereal and oilseed crops in western Canada, 3,6-dichloropicolinic acid has been shown to provide excellent control of C, arvense topgrowth and regrowth in rapeseed {Brassica campestris L,) (O'Sullivan & Kossatz, 1982) and cereals (O'Sullivan & Kossatz, unpublished data). Studies on the absorption and translocation of this herbicide by Turnbull (1981) demonstrated that '''C-3,6-dichloropicolinic acid moved to the apex and root of C. arvense.…”
Section: Absorption Et Translocation De I'acide 36-dichloropicoliniqmentioning
confidence: 99%
“…Cirsium arvense (L.) Scop, (Canada thistle) and Polygonum convolvulus (L.) (wild buckwheat), members of the Compositae and Polygonaceae families, respectively, cause severe yield reductions in canola and cereal crops grown in western Canada (Moore, 1975;O'Sullivan & Kossatz, 1982;Hume, Martinez & Best, 1983). Canada thistle, considered to be the most serious perennial weed in western Canada, can be controlled with a variety of different herbicides, however, complete kill of its spreading pierennial root system is hard to achieve (Friesen, 1968), It is approximately 3 4 times more competitive than wild oat and will reduce barley yields by approximately 30% at an infestation level of 20 shoots m - (O'Sullivan et al, 1982), In the province of Alberta, it is estimated that 35% of all cultivated fields have Canada thistle infestations of at least 5 shoots m-2 (O'Sullivan et al, 1982), Wild buckwheat, an annual weed occurring throughout North America, causes harvesting difficulties and grain contamination because of its characteristic twining growth habit and prolific achene production (Hume er a/., 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Clopyralid, a member of the pyridine family of herbicides, is registered for use in Europe and North America for the selective control of weeds belonging to the Compositae and Polygonaceae families (Hall & Vanden Bom, 1988), Members of the Cruciferae and Gramineae families, particularly rapeseed and cereal crops, are quite tolerant to clopyralid (O'Sullivan & Kossatz, 1982;Hall & Vanden Born, 1988). Clopyralid is rapidly absorbed and translocated in susceptible species (O'Sullivan & Kossatz, 1984;Devine & Vanden Born, 1985;Hall & Vanden Bom, 1988) and is particularly effective for the control of Canada thistle (O'Sullivan & Kossatz, 1982) and wild buckwheat. Furthermore, no herbicide other than clopyralid can provide effective, long-term control of Canada thistle infestations in canola crops.…”
Section: Introductionmentioning
confidence: 99%
“…in canola (Brassica campestris L. and Brassica na-pusL.) (O'Sullivan and Kossatz 1982) and barley (Hordeum vulgare L.) (O'Sullivan and Kossatz 1984). Canada thistle is a serious weed of cereal and oilseed crops in Western Canada (Friesen 1968) and, at the present time, there are no herbicides registered which will provide effective selective control of the aboveground and underground organs in cereal and oilseed crops.…”
mentioning
confidence: 99%